2020
DOI: 10.1063/1.5136079
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state and force fields for Feynman–Hibbs-corrected Mie fluids. II. Application to mixtures of helium, neon, hydrogen, and deuterium

Abstract: We extend the SAFT-VRQ Mie equation of state, previously developed for pure fluids [Aasen et al., J. Chem. Phys. 151, 064508 (2019)], to fluid mixtures of particles interacting via Mie potentials with Feynman-Hibbs quantum corrections of first (Mie-FH1) or second order (Mie-FH2). This is done using a third-order Barker-Henderson expansion of the Helmholtz energy from a non-additive hard-sphere reference system. We survey existing experimental measurements and ab initio calculations of thermodynamic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 62 publications
2
6
1
Order By: Relevance
“…The MD results suggest that γ VL1 = γ L1L2 = 27.93 mN/m at T UCEP . One possible reason for the overprediction of seen by the SGT is attributed to the fact that in general, while the SAFT-VR Mie model excels at predicting pure component critical points, it overestimates the critical condition of the mixtures [42]. The theoretical extrapolations are also in good agreement to ones reported by Cornelisse et al, [20] who calculated the IFTs from SGT combined to the Peng-Robinson and the APACT EoS.…”
Section: Interfacial Tension Along a Three-phase Equilibriumsupporting
confidence: 77%
“…The MD results suggest that γ VL1 = γ L1L2 = 27.93 mN/m at T UCEP . One possible reason for the overprediction of seen by the SGT is attributed to the fact that in general, while the SAFT-VR Mie model excels at predicting pure component critical points, it overestimates the critical condition of the mixtures [42]. The theoretical extrapolations are also in good agreement to ones reported by Cornelisse et al, [20] who calculated the IFTs from SGT combined to the Peng-Robinson and the APACT EoS.…”
Section: Interfacial Tension Along a Three-phase Equilibriumsupporting
confidence: 77%
“…It is noted that the simulations and the equation of state should provide, by design, the same resulting volumetric properties over a wide range of parameters capable of representing both simple and very asymmetric mixtures. However, the results shown here and other recently reported in the literature (see for instances Aasen et al 63 and Zheng et al 64 ) suggest that the critical region of mixtures is not accurately captured by the equation of state in a pressure -explicit representation. While this is a common feature of classical analytical equation of state, SAFT-VR-Mie includes a third order perturbation correction that allows the accurate depiction of the critical region for the monomer term.…”
Section: Discussioncontrasting
confidence: 66%
“…This paper is the first in a series of two, where Paper II will be devoted to mixtures. 69 We demonstrated that the SAFT-VRQ Mie EoS reproduces accurately results from Monte Carlo simulations for generic Mie-FH1 and Mie-FH2 fluids, where it displays a similar accuracy as the present state-of-the-art for classical Mie fluids. We next exploited the link between the EoS and the interaction potentials to find the optimal force-field parameters to represent the thermodynamic properties of neon, helium, normal-hydrogen, orthohydrogen, para-hydrogen, and deuterium.…”
Section: Discussionsupporting
confidence: 60%